A structural equation model on english learning self of middle school students in China's ethnic minority populated area - Xuan, Yunyun; Xie, Xiao; Nimehchisalem, Vahid (Academy Publication, 2023)
As the L2 Motivational Self System (L2MSS) is premised on monolingualism, which ignores the cross-cutting properties of multilingual environments, this study investigates the English Learning Self and its structural characteristics of students in a junior high school in a minority-inhabited area of Guizhou Province, China. These ethnic minority students not only learn their native language (minority languages), but also learn Mandarin Chinese, through which they learn English as their third language, with features of low English proficiency, weak motivation to learn English, and low frequency of English use. Data were collected from 159 Han Chinese students and 274 ethnic minority students in the eighth grade of the junior high school. Structural equation modelling revealed that the Ideal English Self contains three factors: Ideal English Learner, Ideal English Career and Ideal English User, and the most significant Ideal English Self exhibited by the middle school students was Ideal English Learner; while the Ought-to English Self contains three factors: Meeting Other’s Expectation, Self’s Future Expectation and Self’s Present Demand, with Meeting Other’s Expectation marking contributed the most. Through comparative analysis, this study further found that there was no significant difference between local Han Chinese students and ethnic minority students in terms of English Learning Self.